Life cycle assessment and supply chain visibility in Nigeria maritime university, South-South Nigeria - Ikenna Christopher Ugwu; Kelechi Ugwu; Jude Aleakhue; Utibe Mbuk (YAYASAN MITRA PERSADA NUSANTARA, 2026)
Limited knowledge and awareness on green procurement policies among procurement officers, end users, and suppliers constitute obstacles to its effective implementation. The study investigates the relationship between product life cycle monitoring and real- time data sharing in Nigerian Maritime University. The total population of the study comprised of 1,252 employees, and sample size was determined using taro Yamane formula and calculated as 303. The study employed a descriptive survey research design, and a stratified random sampling technique in the distribution of the survey to ensure optimum allocation of survey to each stratum. The study population includes: procurement officers, internal auditors, logistics managers, administrative staff, and heads of departments. Out of 303 questionnaires distributed only 281 were returned and utilized while the remaining 22 were not returned and utilized for the study. Statistical tools such as descriptive, inferential statistics, and linear regression were used to analyze the hypotheses at 5 % significant level. The findings showed that the combined use of life cycle assessment and real-time visibility has a significant impact on better organizational and environmental performance. The study recommend that university management should organize regular training programmes to improve skill development of lecturers, researchers, technical staff, and students on LCA software (e.g., SimaPro, OpenLCA, GaBi) and real-time visibility technologies.